Enhancing the mechanical strength of Multi Jet Fusion–printed polyamide 12 and its glass fiber-reinforced composite via high-temperature annealing - Liu, Xiaojiang (2022)
Multi Jet Fusion (MJF) is a pioneering and highly efficient powder bed fusion additive manufacturing technique. However, even with the addition of reinforced glass fibers (GFs), MJF-printed polyamide 12 (PA12) objects still have lower mechanical strength as compared to many commercial polymer composites. In this work, a high-temperature (173 °C, near the onset melting temperature of PA12) annealing process is developed to remarkably enhance the mechanical strength of MJF-printed PA12 and GF/PA12 composites. Specifically, the ultimate tensile strength (UTS)/tensile modulus of PA12 and GF/PA12 specimens are increased by 20.8%/48.5% and 22.8%/30.6%, respectively. The mechanical performance of GF/PA12 specimens is better than that of previously reported MJF- and Selective Laser Sintering (SLS)-printed PA12, glass bead/PA12, and GF/PA12 composites. Moreover, the melting temperatures of both PA12 and GF/PA12 specimens are increased by more than 5 °C after the annealing process. Further experimental results reveal that the crystallinity increase is the primary enhancement mechanism of the high-temperature annealing. It is envisioned that a similar approach can also be applied to other SLS- and MJF-printed polymers and composites for mechanical enhancement.